Teologia e currículo: Multiculturalismo e cidadania como parâmetros para a elaboração do currículo teológico nas instituições de tradição protestante - NUNES, Élton de Oliveira (2006)
The Education Ministry has officially recognized the Theological area as a primary characteristic of superior education. This recognition has materialized after the new law of Lines of Direction and Bases (LDB) and the 241/99 opinion of the National Education Council, which accredited this area as a superior graduation course, receiving the same handling of other superior courses supported by the LDB. In order to attend to this new reality, it is necessary to obey the requirement of the Education Ministry that, with several steps, requires the elaboration of a main curriculum for the course. This dissertation shows the possible problems of elaborating a curriculum from two orienting axles: the multicultural blend and the citizenship, considering, as the central axle, the National Education Council understanding that the Theological courses, in order to reach their credentials, must present a pedagogical project and the curricular matrix with a theological proposal according to the respective theological tradition. The subject of this research is the interaction possibility/impossibility of two educational axles, the multicultural blending and the citizenship, being used to guide the elaboration of a curricular matrix on the theological area. Thefore, it is based on Paulo Freire’s educational philosophy (as a theoretical reference) of the meeting/dialog/release. Starting from Freire’s thoughts, the author has chosen the multicultural guideline called inter-culturalism, understood and defined as multicultural vision, which privileges the citizens in their cultural micro and macro relations and considers new strategies for relationship and interchange, and has, as a purpose, to promote the construction of social ideas, the recognition of cultural differences and sustainance of their critical and solidary relation. Following this referential, it was chosen a specific concept of citizenship, being understood as critical conscience and way of expression of the rights and duties of a people, through the respect for its expressions of life that are revealed in its culture. With these established points, it was possible to dialogue and to approach the theology, demonstrating the common historical and philosophic origin between the humanist source of the Protestant Theology and the democratic modern chains, and how they have dialogue in the western world (AU)